Field reports, spring 98, Dennis Thompson - Thompson, Denniset al (1998)
An annotated list of birds sighted by Dennis Thompson. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1998. Epson - sheet feed